Trend of Agricultural Production in India in the Post-Reforms Period: A Growth Rate Perspective - Pia Ghoshal (Business, Management and Economics: Research Progress Vol. 2, 2024)
Agriculture is of particular importance in a majority of countries of the world despite their various agendas to achieve the targets of food security and poverty reduction. Indian agriculture’s share of GDP declined to approximately 15% in 2023 compared to 35% in 1990-91. As this has occurred due to the rapid expansion of the secondary and tertiary sectors, it shows that the Indian economy is strongly on the path of development, where the share of agriculture is expected to decline. The current statistics also revealed that employment in the agricultural sector has declined over the years. This can raise questions about the potential of this sector to meet the objectives of providing food security and earning foreign exchange. As agriculture has a historical past with respect to its performance which is expected to have an effect on the present, the objective of this chapter is to analyze the growth performance of the agricultural sector in India in the post-reform period with particular reference to the pre-pandemic phase. Our study has shown that though the growth of this sector has fluctuated over the years and the subsectors have exhibited heterogeneous growth rates over the past two decades, it has steadily recovered in a majority of the cases, thus not compromising with the food availability of the country. Agricultural production has increased in absolute figures over the years, which speaks strongly about an increase in productivity.